A Negative Actor Engagement Scale for Online Knowledge-Sharing Platforms. Issue 1 (February 2023) - Li, Loic Pengtao; Frethey-Bentham, Catherine; Juric, Biljana; Brodie, Roderick J.
Prior research shows that negative engagement is conceptually different from positive engagement, and necessitates further understanding and measurement instruments. This study reports a series of four studies leading to conceptualization, development, and validation of a negative actor engagement scale for online knowledge-sharing platforms. An online learning service platform Piazza is chosen as the research context, where learners engage intensively in knowledge-sharing with one another as well as instructors. We conceptualize negative engagement as actors' negative engagement dispositions (i.e., negative emotions and cognitions) during interactions on the platform. Negative engagement disposition is shown to be a second-order formative construct comprising four first-order reflective constructs—annoyance, social anxiety, failed expectations, and futility. The relationship between negative engagement disposition and its behavioral consequence of negative word-of-mouth is established. This is the first study to conceptualize and operationalize negative actor engagement.